ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI KECANTKAN 2 SMKN 6 PADANG - Rizka Susilawati; Radhya Yusri; Lucky Heriyanti Jufri (Jurnal Karya Pendidikan Matematika, 2023)
This research is motivated by the low ability of students to solve mathematical problems. The purpose of this study was to find out how the ability to solve mathematical problems of class XI Beauty 2 students at SMKN 6 Padang. This type of research is descriptive research with a quantitative approach. The sampling technique used purposive sampling. The subjects of this study were students of Class XI Beauty 2 SMKN 6 Padang. The research instrument used was a test of ability to solve mathematical problems and interviews. Data analysis of students' mathematical problem solving ability was described based on the results of the mathematical problem solving ability test and interview analysis. The results of this study indicate that the indicator for understanding the problem is obtained by 46% in the low category, the indicator for compiling a settlement plan is obtained by 47% in the low category, the indicator for completing the settlement plan is 46% in the low category and for the indicator of re-choosing the answer obtained is 28% in the low category. So it can be concluded that there are no students who have the ability to solve mathematical problems which are included in the high criteria.